Cutting export subsidies, cropping domestic production: input-output analysis of the Swiss dairy sector after abolishment of the ‘Chocolate law’ subsidies - Seyhan KÂHYA; Aleš KUHAR (Acta Agriculturae Slovenica)
The `Chocolate law’ in Switzerland enables subsidies for dairy and wheat farmers, bound to the condition that their products are exported after processing (Swiss Federation, 2011). Though the Ministerial Conference of the World Trade Organization has decided in December 2015 that this law has to be abolished by 2021 [WTO, 2015]. Cutting subsidies might lead to a demand shock and consequently a cropped domestic production (Miller and Blair, 1985). We analysed in this study the interdependence of the agro-food sectors by a Leontief input-output model and their linkages to other sectors (Chereny and Watanabe, 1958, Leontief 1986) and additionally, the amount, direction and dispersion of the possible demand shock.  Hence, non-meat food processors and dairy processing were determined as key sectors as they have strong linkage effects and are rather concentrated to few sectors. Both sectors rely strongly on the output of the raw milk producers and have few sectors to sell their products. Outside of the cut sectors, these sectors will be challenged the most from this new policy.